2011
DOI: 10.3109/01443615.2011.581319
|View full text |Cite
|
Sign up to set email alerts
|

How do urogynaecologists treat failed suburethral slings? Experience from the British Society of Urogynaecology database and literature review

Abstract: Midurethral urethral sling (MUS) procedures have high success and satisfaction rates. A small percentage of MUS operations will fail and most centres have limited experience of treating this outcome. The aim of this study was to review the British Society of Urogynaecology (BSUG) database for women who underwent repeat anti-incontinence surgery after failed MUS. A total of 313 repeat surgical procedures were identified. For any failed MUS, the commonest second surgical intervention was a repeat retropubic MUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…This finding was similar to that of a 2011 publication looking at the British Society of Urogynaecology database where 54% of patients with recurrent SUI had a repeat retropubic midurethral sling 18 . Nevertheless, it must be emphasised that the cure rates after a second procedure tend to decline and the risk of de novo overactive bladder syndrome rises 19 .…”
Section: Discussionsupporting
confidence: 86%
“…This finding was similar to that of a 2011 publication looking at the British Society of Urogynaecology database where 54% of patients with recurrent SUI had a repeat retropubic midurethral sling 18 . Nevertheless, it must be emphasised that the cure rates after a second procedure tend to decline and the risk of de novo overactive bladder syndrome rises 19 .…”
Section: Discussionsupporting
confidence: 86%
“…We chose to use an autologous facial sling to salvage a failed mesh midurethral sling in order to avoid repeating the same operation while hoping for a different outcome. Many surgeons choose to repeat a type of sling after a failed sling . Nevertheless, there is a paucity of data to strongly recommend one salvage treatment over another, and treatments that are usually considered in this clinical setting include bulking agents; retropubic suspension; and repeat, midurethral or retropubic sling .…”
Section: Discussionmentioning
confidence: 99%
“…Repeat midurethral tape has gained popularity over the last few years, and a recent survey among general gynecologists and urogynecologists [30] and a review of a national database in the UK [31] showed that it is the secondary procedure of choice for persistent or recurrent SUI after a failed tape. Small retrospective studies for retropubic tapes (TVT) following a failed midurethral tape have shown subjective cure rates of 71-92% [9][10][11] and objective cure rates of 55-77% [10,12].…”
Section: Discussionmentioning
confidence: 99%